Cured nasopharyngeal carcinoma stage IV with Haemostatic-intent radiotherapy - Mohamad, Irfan; Manan, Aifaa Abdul; Rao, Vengatesh; Bahavaraju, Venkatesh Murali Krishna (Bangladesh Journal of Medical Science, 2016)
Nasopharyngeal carcinoma (NPC) is known to present with nasal and aural symptoms. Sometimes neck mass and cranial nerve palsies can be the presenting symptom. Frank epistaxis is relatively rare. Advanced stage disease is usually treated with concurrent chemoradiotherapy. We are reporting a case of NPC patient presented complete nasal obstruction with frank epistaxis. The bleeding was stopped and the disease cured with hemostatic-intent radiotherapy. Bangladesh Journal of Medical Science Vol.15(3) 2016 p.480-482